Examining the structure and behavior of Afghanistan's routine childhood immunization system using system dynamics modeling. Issue 3 (4th September 2017) - Schuh, Holly B.; Merritt, Maria W.; Igusa, Takeru; Lee, Bruce Y.; Peters, David H.
Abstract : Purpose: The purpose of this paper is to demonstrate how public health and systems science methods can be combined to examine the structure and behavior of Afghanistan's routine childhood immunization system to identify the pathways through which health system readiness to deliver vaccination services may extend beyond immunization outcomes. Design/methodology/approach: Using findings from an ecological study of Afghanistan's immunization system and a literature review on immunization program delivery, the routine immunization system was mapped using causal loop diagrams. Next, a stock-and-flow diagram was developed and translated to a system dynamics (SD) model for a system-confirmatory exercise. Data are from annual health facility assessments and two cross-sectional household surveys. SD model results were compared with measured readiness and service outcomes to confirm system structure. Findings: Readiness and demand-side components were associated with improved immunization coverage. The routine immunization system was mapped using four interlinking readiness subsystems. In the SD model, health worker capacity and demand-side factors significantly affected maternal health service coverage. System readiness components affected their future measures mostly negatively, which may indicate that the reinforcing feedback drives current system-structured behavior. Originality/value: The models developed herein are useful to explore the potential impact of candidate interventions on service outcomes. This paper documents the process through which public health and systems investigators can collaboratively develop models that represent the feedback-driven behavior of health systems. Such models allow for more realistically addressing health policy and systems-level research questions.